Using a Smartphone Application to Promote Healthy Dietary Behaviours and Local Food Consumption. (25th August 2015) - Gilliland, Jason; Sadler, Richard; Clark, Andrew; O'Connor, Colleen; Milczarek, Malgorzata; Doherty, Sean
Abstract : Smartphone "apps" are a powerful tool for public health promotion, but unidimensional interventions have been ineffective at sustaining behavioural change. Various logistical issues exist in successful app development for health intervention programs and for sustaining behavioural change. This study reports on a smartphone application and messaging service, called "SmartAPPetite, " which uses validated behaviour change techniques and a behavioural economic approach to "nudge" users into healthy dietary behaviours. To help gauge participation in and influence of the program, data were collected using an upfront food survey, message uptake tracking, experience sampling interviews, and a follow-up survey. Logistical and content-based issues in the deployment of the messaging service were subsequently addressed to strengthen the effectiveness of the app in changing dietary behaviours. Challenges included creating relevant food goal categories for participants, providing messaging appropriate to self-reported food literacy and ensuring continued participation in the program. SmartAPPetite was effective at creating a sense of improved awareness and consumption of healthy foods, as well as drawing people to local food vendors with greater frequency. This work serves as a storehouse of methods and best practices for multidimensional local food-based smartphone interventions aimed at improving the "triple bottom line" of health, economy, and environment.